PERSIDANGAN ELEKTRONIK (E-LITIGASI) PADA PERADILAN TATA USAHA NEGARA - Agus Salim; Elfran Bima Muttaqin (Paulus Law Journal, 2020)
The State Administrative Judicial as the executor of judicial power has a duty and authority to examine, decide, and resolve State Administrative disputes. Along with tecnological development, judicial practices within the scope of the Indonesian Supreme Court hal implemented the ecourt application. The aims of this study is to analyze policies regarding the implementation of Electronic Litigation in the State Administrative Judicial, as well as to find the obstacles encountered. This study uses a normative method with a statute approach, that is Act 5 in 1986 concerning State Administrative Judicial and its amendment, and Supreme Court Regulation Number 1 of 2019 concerning Administration of Cases and Trials in Court Electonically. The result of the study show that the application of Electronic Litigation at State Administrative Judicial is carried out comprehensively, that is from the registration stage until reading of judicial decisions. The obstacles that still being faced are related to the stage of evidence which in practice still requires a conventional trial, and the limited access to the internet network in several regions in Indonesia.